(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current state of changes in alcohol consumption awareness among the elderly using a health belief model in Nam Dinh city, 2025. Subjects and methods: A descriptive cross-sectional study of 410 elderly individuals on changes in alcohol consumption awareness and intervention compared before and after. Results: The 60-80 age group accounted for the majority (85.1%), with more men than women (63.7%), and high school or vocational school education or lower (90.5%). Elderly individuals were clearly aware of the health barriers associated with alcohol consumption, with sensitivity at 94.9%; motivation to change habits at 98%. After the intervention, elderly individuals were clearly aware of the risks associated with health barriers, sensitivity, and motivation to change alcohol consumption habits at 94.4%; awareness of alcohol consumption improved significantly after the HBM intervention through barrier scores; the severity level decreased from 13.05 points to 12.08 points (p < 0.001), the perception of health benefits decreased from 10.19 points to 8.24 points (p < 0.001), and the motivation to change behavior decreased from 10.29 points to 8.23 points ​​(p < 0.001). Conclusion: The health belief model promotes increased motivation, strengthens beliefs about health benefits, and supports habit change, bridging the gap between perception and behavior.